Impedance analysis of oil conductivity and pixel non-uniformity in electrowetting displays - Bojian Xu; Yuanyuan Guo; Jitesh Barman; Ben H. Erné; Yong Deng; Guofu Zhou; Jan Groenewold (Results in Physics, 2020)
The electrical conductivity of the oil film is a key property of electrowetting displays (EWD) and its evolution probably correlates to the device lifetime. In this report, we fabricate an EWD device and measure its electrical impedance spectrum. The experimental results inform on the electrical resistivity of the oil film, as revealed by comparison with numerical simulations based on an equivalent electrical circuit model. Wide distribution in the oil-film resistance has to be incorporated into the model to reproduce the measured impedance spectrum precisely, which supports previous work indicative of pixel-to-pixel variation in the oil film electrical conductivity. Our work demonstrates that one can conveniently characterize the oil film resistance and its non-uniformity using electrical impedance spectroscopy.